Leadership’s Policy in Pandemic School Era: New Student Admission, Zonation System, and Digital Problem - Samsu Samsu (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2021)
This study discusses the leadership of school principals in the context of new student admissions by zonation system, and tracking digital problems in the pandemic era. This study aims to analyze how technology responds to policies related to new student admissions in the Covid-19 era. A qualitative approach is used. researcher as an active instrument. Data related to leadership policies, intake of new students, and digital problems were obtained through interviews, observations, and documentation with data flow chart analysis by Miles and Huberman. The informants are the principal, deputy principal, student affairs, administration, and school operators. The findings show that the acceptance of new students at MAN 2 Jambi City takes into account the number of teachers, and facilities according to the on-line PPDB technical instructions. The on-line 2020/2021 PPDB acceptance is intended to apply 2 channels, namely the